Gel-based morphological design of zirconium metal–organic frameworks. Issue 5 (29th March 2017) - Bueken, Bart; Van Velthoven, Niels; Willhammar, Tom; Stassin, Timothée; Stassen, Ivo; Keen, David A.; Baron, Gino V.; Denayer, Joeri F. M.; Ameloot, Rob; Bals, Sara; De Vos, Dirk; Bennett, Thomas D.
Abstract : The ability of zirconium metal–organic frameworks (MOFs) to gelate under specific synthetic conditions opens up new opportunities in the preparation and shaping of hierarchically porous MOF monoliths, which could be directly implemented for catalytic and adsorptive applications. Abstract : The ability of metal–organic frameworks (MOFs) to gelate under specific synthetic conditions opens up new opportunities in the preparation and shaping of hierarchically porous MOF monoliths, which could be directly implemented for catalytic and adsorptive applications. In this work, we present the first examples of xero- or aerogel monoliths consisting solely of nanoparticles of several prototypical Zr 4+ -based MOFs: UiO-66-X (X = H, NH2, NO2, (OH)2 ), UiO-67, MOF-801, MOF-808 and NU-1000. High reactant and water concentrations during synthesis were observed to induce the formation of gels, which were converted to monolithic materials by drying in air or supercritical CO2 . Electron microscopy, combined with N2 physisorption experiments, was used to show that irregular nanoparticle packing leads to pure MOF monoliths with hierarchical pore systems, featuring both intraparticle micropores and interparticle mesopores. Finally, UiO-66 gels were shaped into monolithic spheres of 600 μm diameter using an oil-drop method, creating promising candidates for packed-bed catalytic or adsorptive applications, where hierarchical pore systems can greatly mitigate mass transfer limitations.